A miniature flapping mechanism using an origami-based spherical six-bar pattern - Bae, Seung Yong; Koh, Je Sung; Jung, Gwang Pil (Applied Sciences (Switzerland), 2021)
In this paper, we suggest a novel transmission for the DC motor-based flapping-wing micro aerial vehicles (FWMAVs). Most DC motor-based FWMAVs employ linkage structures, such as a crank-rocker or a crank-slider, which are designed to transmit the motor’s rotating motion to the wing’s flapping motion. These transmitting linkages have shown successful performance; however, they entail the possibility of mechanical wear originating from the friction between relative moving components and require an onerous assembly process owing to several tiny components. To reduce the assembly process and wear problems, we present a geometrically constrained and origami-based spherical six-bar linkage. The origami-based fabrication method reduces the number of the relative moving components by replacing rigid links and pin joints with facets and folding joints, which shortens the assembly process and reduces friction between components. The constrained spherical six-bar linkage enables us to change the motor’s rotating motion to the linear reciprocating motion. Due to the property that every axis passes through a single central point, the motor’s rotating motion is filtered at the spherical linkage and does not transfer to the flapping wing. Only linear motion, therefore, is passed to the flapping wing. To show the feasibility of the idea, a prototype is fabricated and analyzed by measuring the flapping angle, the wing rotation angle and the thrust.
Keywords: Bio-inspired robot; Flapping mechanism; Micro aerial vehicle